2022
DOI: 10.1186/s12935-022-02645-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in tumor microenvironment: novel therapeutic targets

Abstract: Bioactive lipid molecules have been proposed to play important roles linking obesity/metabolic syndrome and cancers. Studies reveal that aberrant lipid metabolic signaling can reprogram cancer cells and non-cancer cells in the tumor microenvironment, contributing to cancer initiation, progression, metastasis, recurrence, and poor therapeutic response. Existing evidence indicates that controlling lipid metabolism can be a potential strategy for cancer prevention and therapy. By reviewing the current literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 153 publications
0
13
0
Order By: Relevance
“…Cancer cells use lipid metabolism to obtain energy, biofilm components, and signaling molecules needed for proliferation, survival, invasion, metastasis, tumor response, and cancer treatment. Numerous studies showed that lipid metabolism disorders play a key role in the progression of NPs exposure toxicity. , In this experimental group, 18-hydroxyoleate and 9,10-epoxystearic acid were up-regulated and phosphocholine was downregulated, while the levels of the remaining metabolites did not change significantly. Both metabolites in the GNR group were significantly up-regulated, implying that these may help in clearing cancer cells.…”
Section: Resultsmentioning
confidence: 71%
“…Cancer cells use lipid metabolism to obtain energy, biofilm components, and signaling molecules needed for proliferation, survival, invasion, metastasis, tumor response, and cancer treatment. Numerous studies showed that lipid metabolism disorders play a key role in the progression of NPs exposure toxicity. , In this experimental group, 18-hydroxyoleate and 9,10-epoxystearic acid were up-regulated and phosphocholine was downregulated, while the levels of the remaining metabolites did not change significantly. Both metabolites in the GNR group were significantly up-regulated, implying that these may help in clearing cancer cells.…”
Section: Resultsmentioning
confidence: 71%
“…Lipid metabolism in tumor cells and stroma has been linked to tumor progression and drug resistance. 46,47 It is also noteworthy that endothelial expression of FABP4, PRCP, and KLF4, which are upregulated after chemotherapy, has been linked to vascular injury repair. 48,49 Thus these genes may represent potential targets for anti-angiogenic therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, genes and subpopulations associated with lipid uptake and metabolism were upregulated in the post‐treatment fibroblasts and endothelial cells. Lipid metabolism in tumor cells and stroma has been linked to tumor progression and drug resistance 46,47 . It is also noteworthy that endothelial expression of FABP4 , PRCP , and KLF4 , which are upregulated after chemotherapy, has been linked to vascular injury repair 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…PUFAs, especially LC-PUFAs such as arachidonic acid (AA), eicosatetraenoic acid (EPA), and docosahexaenoic acid (DHA), are important signaling molecules and key components of biomembrane phospholipids (22,23). PUFAs and their derivatives have been implicated to play broad functions in cancer impacting various stages from tumorigenesis to progression and metastasis (24)(25)(26)(27)(28). Previous research has shown that Fatty Acid Desaturase 1 (FADS1), a rate-limiting enzyme in LC-PUFA bioproduction, plays a significant role in the growth of various cancer cells (13) and is overexpressed in colon, pancreas, breast, and laryngeal cancers (29).…”
Section: Introductionmentioning
confidence: 99%